Moving vehicle noise classification using backpropagation algorithm - Norasmadi, Abdul Rahim; Paulraj, Murugesa Pandiyan, Assoc. Prof.; Abdul Hamid, Adom, Assoc. Prof. Dr.; Sundararaj, Sathishkumar (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/